Distribution patterns of phosphorylated Thr 3 and Thr 32 of histone H3 in plant mitosis and meiosis - Caperta, A. (2011)
Cell cycle dependent phosphorylation of conserved N-terminal tail residues of histone H3 has been described in both animal and plant cells. Through cytogenetic approaches using different plant species we show a detailed description of distribution patterns of phosphorylated histone H3 at either threonine 3 or threonine 32 in mitosis and meiosis. In meristematic cells of the large genome species Secale cereale, Vicia faba and Hordeum vulgare we have found that phosphorylation of both threonine residues begins in prophase, and dephosphorylation occurs in late anaphase. However, in the small genome species Arabidopsis thaliana dephosphorylation occurs at anaphase. In the first division of meiosis of species with large genomes phosphorylation of histone H3 at either threonine 3 or threonine 32 is seen first in diakinesis and extends to anaphase I, whereas in the second division these post-translational modifications are visible at metaphase II through anaphase II. While in A. thaliana dephosphorylation takes place at anaphase I and II. In all species analysed phosphorylated H3 at either threonine 3 or threonine 32 are distributed along the entire length of chromosomes during mitotic metaphase and metaphase I. In the second meiotic division threonine 3 phosphorylation is restricted to the pericentromeric domain, while phosphorylation of threonine 32 is widespread along chromosome arms of all species analysed.